The Effect Of Giving Red Dragon Fruit (Hylocereus polyrhizus) Extract On Spermatozo Motility In White Rats (Rattus norvegicus) Wistar Line With High Fat Induction - Nuranisa, Kirani; Cut Fauziah; Yuli Suciati (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2020)
Hyperlipidemia is a condition when high level of blood lipids and causes morphologicalchanges in spermatozoa. Red dragon fruit (Hylocereus Polyrhizus) is one of the plantsas a source of antioxidants and has unsaturated fat content that is needed in thespermatozoa maturation process. The aims of this the study is to determine the benefitsof red dragon fruit extract on the motility of white rat spermatozoa (Rattus norvegius)induced by high-fat diet. The study is design by true experimental research andresearch only testing group design. This research conducted in the Pharmacology andTherapy Laboratory, Padjajaran University Education Hospital, in January 2020 usingwhite rats, male . Â± 8 weeks wistar strains weighing Â± 200-250. The study sample wasdivided into several groups such group I as a control, group II as a negative control,group III as positive group with simvastatin dose 0.72 mg / day, group IV as researchgroup 1 using red dragon fruit extract dose of 60 mg / 200 grBB / day for 52 days, andgroup V as group 2 therapy using dragon fruit extract dose of 60 mg / 200grBB / dayfor 104 days. The results showed that the mean percentage of motility of ratspermatozoa increased in the relief group with the supplement of red dragon fruitextract by dosing of 60 mg / 200 grBB / day for 104 days, or 51, 2%. This studyconclude that red dragon fruit has a superior effectivity better than simvastatin inincreasing the motility of spermatozoa.